2017
DOI: 10.7717/peerj.3953
|View full text |Cite
|
Sign up to set email alerts
|

Male sex pheromone components in Heliconius butterflies released by the androconia affect female choice

Abstract: Sex-specific pheromones are known to play an important role in butterfly courtship, and may influence both individual reproductive success and reproductive isolation between species. Extensive ecological, behavioural and genetic studies of Heliconius butterflies have made a substantial contribution to our understanding of speciation. Male pheromones, although long suspected to play an important role, have received relatively little attention in this genus. Here, we combine morphological, chemical and behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
133
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(146 citation statements)
references
References 76 publications
(97 reference statements)
11
133
1
1
Order By: Relevance
“…Backcross hybrid females between H. cydno and H. melpomene are less likely to mate when they are heterozygous at the locus controlling a colour pattern element on the hindwing than when homozygous, suggesting a potential genetic component to female choice between species (Merrill, Schooten, Scott, & Jiggins, 2011). In Heliconius timareta, H. erato and two subspecies of H. melpomene, females are less likely to mate with males whose pheromone-producing androconial scales have been blocked with nail varnish than with non-blocked males (Darragh et al, 2017). Similarly, perfuming conspecific males with another species' pheromones reduced the likelihood of females mating with them (Mérot, Frérot, Leppik, & Joron, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Backcross hybrid females between H. cydno and H. melpomene are less likely to mate when they are heterozygous at the locus controlling a colour pattern element on the hindwing than when homozygous, suggesting a potential genetic component to female choice between species (Merrill, Schooten, Scott, & Jiggins, 2011). In Heliconius timareta, H. erato and two subspecies of H. melpomene, females are less likely to mate with males whose pheromone-producing androconial scales have been blocked with nail varnish than with non-blocked males (Darragh et al, 2017). Similarly, perfuming conspecific males with another species' pheromones reduced the likelihood of females mating with them (Mérot, Frérot, Leppik, & Joron, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in many taxa, male choice has been much more commonly studied than female choice in Heliconius, because male choice is easier to test with model females as stimuli and because male choice is the first step in mating interactions. Female choice studies have almost exclusively documented mate preference for variation (natural or experimentally induced) in conspecific males (Chouteau, Llaurens, Piron-Prunier, & Joron, 2017;Darragh et al, 2017;Finkbeiner, Fishman, Osorio, & Briscoe, 2017). However, males still regularly court heterospecific females when they have the opportunity (Merrill, Gompert, et al, 2011) and researchers have generally found stronger assortative mating between species when there is the potential for female choice in the experimental design (Mérot, Salazar, Merrill, Jiggins, & Joron, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the existence of closely related, sympatric taxa that do not differ in mimetic pattern suggests that mating cues other than color pattern are also important (Giraldo et al 2008). For example, recent studies have demonstrated a role for pheromones in mediating mate choice (Mérot et al 2015;Darragh et al 2017). Divergent host plant and habitat use have also been proposed as sources of reproductive isolation (Estrada and Jiggins 2002;Rosser et al 2019), and adaptations to environmental gradients have been linked to speciation (Jiggins et al 1996;Mérot et al 2013).…”
mentioning
confidence: 99%
“…This indicates that there must be additional cues, such as behavioral or pheromonal differences that allow species recognition/discrimination even when the butterflies look virtually the same (Mérot, Frérot, Leppik, & Joron, 2015). Nonvisual stimuli could serve both to enhance probabilities of intraspecific mating and to deter interspecific mating (Darragh et al., 2017; Friberg et al., 2008). Experiments testing only the visual component of mate choice using paper wing models, or using freshly emerged virgin females that may not have a full behavioral repertoire, are therefore not only artificial, but do not present a complete assessment of potential components of mate choice and/or discrimination.…”
Section: Resultsmentioning
confidence: 99%